Tri Hita Karana-based conservation initiatives: Empowering salt farmers and fostering sustainable economic practices in Kusamba coastal area - Goca, I Gusti Putu Agung Widya; Sumerta, I Komang; Adiandari, Ade Maharini; Miranti, Riyana; Diatmika, I Kadek Dwi (Journal of Community Service and Empowerment, 2024)
The coastal village of Kusamba in Bali has long relied on salt farming as an economic activity, but conventional methods have harmed the environment. The Tri Hita Karana-Based Conservation Initiatives were developed with community engagement to address this issue. Researchers collaborated closely with local stakeholders to establish an approach that combines tradition, ecological preservation, and economic prosperity. The main findings highlight the implementation of Tri Hita Karana in increasing salt production in order to preserve the traditional salt farming culture. The initiatives include training and mentoring programs on sustainable salt production methods and preserving traditional salt farming. These efforts have led to improved biodiversity, strengthened coastlines, increased income, and sustainable tourism. Challenges faced include resistance to change, which was overcome through dialogue. The initiatives have attracted global recognition and serve as a model for sustainable development. The community's active involvement, alongside scientific knowledge and eco-friendly technologies, contributed to a 30% increase in salt production yield. The initiatives align with Sustainable Development Goals (SDGs) and highlight the significance of holistic conservation approaches. Although successful, challenges such as funding limitations and climate variability persist. In conclusion, the Tri Hita Karana-Based Conservation Initiatives in Kusamba demonstrate the potential of blending tradition and modernity to achieve a balanced and sustainable future, setting an example for other communities and researchers.